Association between consumption of ultra-processed foods and bacterial vaginosis: a case-control study - Morvarid Noormohammadi; Ghazaleh Eslamian; Seyyedeh Neda Kazemi; Bahram Rashidkhani; Fatemeh Omidifar (Mashhad University of Medical Sciences, 2022)
Introduction: Bacterial vaginosis is the most common vaginal infection in women of childbearing age. Identifying nutritional risk factors as a potential therapeutic target can be important. This study was performed with aim to determine the relationship between the consumption of ultra-processed foods and bacterial vaginosis. Methods: This case-control study was performed in 2020 on 144 women with bacterial vaginosis and 151 healthy women aged 15-45 years referred to the gynecology clinic of Imam Hossein Hospital in Tehran. Bacterial vaginosis was diagnosed using the Amsel criteria and participants were divided into case and control groups based on it. Food intake of participants during 1 last year was collected using a valid semi-quantitative food frequency questionnaire with 168 food items. Ultra-processed foods were classified according to the NOVA classification system. A logistic regression test was used to investigate the association between the consumption of ultra-processed foods with bacterial vaginosis, and then the odds ratio was calculated. P< 0.05 was considered significant. Results: After adjusting for confounding variables, it was seen that participants in the upper tertile of intakes of the ultra-processed foods (OR=2.13, CI: 1.19-3.8, P=0.004), processed meats and fast foods (OR=2.27, CI: 1.23-4.2, P=0.008), oils and sauces (OR=2.47, CI: 1.34-4.54, P=0.004) and sweets (OR=2.82, CI: 1.5-5.3 P=0.001) were significantly more likely to be suffering from bacterial vaginosis than the group in first tertile. Conclusion: There was a direct relationship between the intake of ultra-processed foods, processed meats and fast foods, oils and sauces and sweets with bacterial vaginosis.